Idealitas Pancasila dan Realitas Maqashid Syariah - Miskari; Mhd. Syahnan; Hasan Matsum (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study discusses the Unitary State of the Republic of Indonesia, which is not a religious state, but the Pancasila, produced based on a formulation of taste, nobility, customs, culture, religion, and beliefs that exist and grow in Indonesia. Because Pancasila was born from the womb of the Indonesian nation, even though the majority of the population is Muslim, Pancasila has succeeded in establishing itself as the basis of the state, state philosophy, and state ideology for many years now. It shows how powerful and great Pancasila is. However, recently, Pancasila has again clashed with Islam. Pancasila is considered a taghut system, created by infidels, and a secular system that is no longer relevant to the life of the Indonesian nation, which is predominantly Muslim. This research uses a qualitative approach with literature research methods. Primary and secondary data are from books, articles, news, and journals. The theory used in this research is the maqashid sharia approach as a cognitive, open, comprehensive, hierarchical, multidimensional, and purposeful system. Hence, it is found that the ideality of Pancasila rests on the reality of the Indonesian nation's activities in implementing the substantive values of Pancasila and Islam, not on its format. So, it was found that Pancasila and Islam met simultaneously in protecting their people, especially in protecting religion, soul, reason, property, lineage, and honor.